STRATEGI KEHUMASAN PEMPROV BALI DALAM MENGATASI ISU PENJUALAN DAGING ANJING DI BALI - noviyanthi, nirmala (Universitas Pendidikan Nasional, 2018)
ABSTRACTReputation is the important thing to keep in every company. The good or a bad of company’s reputation depends on how the management in that company especially how the public relation’s performance in facing every crisis. Crisis has unexpectedly character and would be worst if it can’t take seriously. One of the crisis that happens in Bali’s government is about the dog-meat trading issue, which is this have been pubished in some foreign media. With this crisis, researcher wanted to research about the strategy in prublic relation’s government in facing this crisis according to method of public relation’s crisis management by Lazarsfeld and Reitz.In this reseacrh, researcher tried to connected the strategy that have been public relations of Bali’s government did with the six steps according to Lazarsfeld and Reitz’s method. The result of this research is The public relation of Bali province government could apply the strategy which have been planned appropriate with method of public relation’s crisis management that be reference of researcher, therefore the result that expected could be achieved by the implementation of that strategy.Keywords : public relation’s crisis management, strategy of public relation.